Effect of 8 weeks CrossFit exercises on high school students during a physical fitness program: Effect of 8 weeks CrossFit exercises - Mime, Mokhtar; Hamzaoui, Hakim; Benchehida, Abdelkader; Cherara, Lalia (Quality in Sport, 2022)
Purpose: The aim of this study was to assess the effectiveness of CrossFit exercises over a period of 8 weeks in a group of high school students during their physical education sessions at the school. and to mitigate the deficits in fitness caused by COVID-19 prevention measures. Material and methods: 94 students subject aged (16– 17) years were randomly allocated into an included 46 students (2nd level:12 men 11 women; 3rd level: 12 men 11 women) and 1 control group included 48 students (2nd level:13 men 11 women; 3rd level: 13 men 12 women Experimental group (EG) that performed the 8 weeks CrossFit exercises and control group (CG). Physical fitness tests were done: lifting straight legs in height (number times); running on the spot with an intensity of 70% of the maximum to severe fatigue (c); "Shuttle" run 4 × 9 m (with); 60 m run (s) and cross twine (cm). Results: there are considering changes, development of the maximum dynamic force endurance, speed abilities, flexibility and mobility in the hip joints of the main groups, In the age aspect, there is mainly the improvement in results with age, both in the main and control groups (p>0,05). Conclusion: the study achieved a significant improvement in the physical condition of the students, also allows to talk about the effectiveness of training, built on the basis of a motivated choice of the target CrossFit high school program.